PENGARUH BEBAN KERJA DAN KEJENUHAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Deni Aditya; Meiske Claudia; Dahniar Dahniar (JWM (JURNAL WAWASAN MANAJEMEN), 2021)
This study aims to examine and to analyze the influence of workload and job burnout to employee performance with organizational commitment as mediation variable (Case Study At PT PLN (Persero) ULPLTD/G Trisakti UPDK Barito). In addition, this study also examined the effect of workload to employee performance with organizational commitment as mediation and the effect of job burnout to employee performance with organizational commitment as mediation. The study was carried out using a sample of 42 PT. PLN (Persero) ULPLTD/G Trisakti UPDK Barito staffs as respondents. The data analysis technique used is path analysis and used PLS (Partial Least Square) to test the hypothesis. The result of this study suggest that workload has a significant effect to employee performance directly or mediated by organizational commitment, organizational commitment has a significant effect on employee performance, and job burnout has a significant effect to employee performance directly or mediated by organizational commitment.